Peran profitabilitas dalam memoderasi pengaruh struktur modal dan kebijakan dividen terhadap nilai perusahaan - Nuswandari, Inti; Wibowo, Edi; Jayadi, Jayadi (Jurnal Akuntansi dan Manajemen, 2026)
This study aims to analyze the role of profitability in moderating the influence of capital structure and dividend policy on firm value. The background of this study is based on the results of previous studies that showed inconsistent findings regarding the influence of capital structure and dividend policy on firm value, as well as differences in results regarding the moderating role of profitability. The research method used was a systematic literature review, examining various national and international scientific articles relevant to the topic from 2020–2025. The results of the study indicate that capital structure and dividend policy influence firm value, but the nature of this influence varies across industries and research periods. Profitability generally has a positive effect on firm value, although some studies report conflicting results. Furthermore, the role of profitability as a moderating variable remains controversial, with some studies demonstrating a reinforcing effect, while others find no moderating effect. This study concludes that the relationship between capital structure, dividend policy, and profitability on firm value is contextual, influenced by industry factors and external conditions such as economic crises. Therefore, further research is needed with a longer period, broader sector coverage, and a more comprehensive methodological approach to obtain more consistent conclusions.